Спин-офф одного комментария: Речь Н. В. Недоброво [Spin-off from an Annotation: A Speech by Nikolai Nedobrovo] - Obatnin, Gennadi (Slavica Revalensia, 2023)
This article examines a series of celebrations dedicated to the 25th anniversary of Konstantin Bal’mont’s literary career. Its major focus is the event that took place on March 11, 1912 in the hall of the Saint Petersburg Governorate zemstvo. The article gives an overview of the details of the event’s organization, its participants, and reflections on the event in the press, emphasizing the fact that Bal’mont’s anniversary became one of the very few reasons that Saint Petersburg artists would unite. It culminates with a previously unpublished draft of the speech by Nikolai Nedobrovo delivered on the occasion.